Sustainable cycling futures: Can cycling be the future? - Psarikidou, K.; Zuev, D.; Popan, C. (Applied Mobilities, 2020)
In a world which is constantly “on the move” (Urry Citation2007), increasing attention has been given to the practice of cycling and its potential contribution to a more sustainable re-configuration of everyday living and moving (Cox Citation2010; May 2013, Sheller; Urry Citation2000). Despite its long history, cycling has been re-introduced as a “new” mobility practice that could configure more sustainable futures, by addressing a wider range of socio-environmental issues: from pollution, congestion, health, disease and climate change to quality of life, community cohesion and poverty alleviation (OECD Citation2004; ITF Citation2016).